Shift work, low-grade inflammation, and chronic pain: a 7-year prospective study - Christensen, Jan Olav (Int Arch Occup Environ Health, 2021)
OBJECTIVES: We investigated prospective associations of shift work with chronic pain and C‐reactive protein (CRP), an indicator of inflammation. Furthermore, we elucidated CRP as a possible mediator and/or moderator of effects of shift work on pain. METHODS: Data from a 7 years follow‐up study were analyzed (N = 2323). Shift work and chronic pain of “neck/shoulder”, “arm/hand”, “upper back”, “low back”, “hip/leg/feet”, and “other regions” were measured by questionnaires. “Chronic widespread pain”, “number of chronic pain sites”, and “any chronic pain” were computed. CRP was measured in serum samples. Logistic and Poisson regressions were conducted. Mediation was assessed by casual mediation analyses and moderation by the Relative Excess Risk due to Interaction (RERI). RESULTS: Shift work was not associated with any chronic pain variable and no mediation was detected. CRP was associated with low back pain, hip/leg pain, and “number of pain sites”, and also with the combination of shift work and CRP of 1–2.99 mg/L (compared to: no shiftwork and CRP < 1). Additionally, shiftwork and CRP 1–2.99 mg/L was associated with risk of “any chronic pain” (OR: 1.76, 95% CI: 1.12, 2.85), which was not associated with CRP alone. Moderation analyses suggested the risks for “any chronic pain” and “number of pain regions” increased when individuals with elevated CRP worked shifts—beyond what the separate effects of CRP and shift would suggest. CONCLUSIONS: We found no evidence of shift work in general affecting CRP or chronic pain. However, shift work and elevated CRP combined may influence chronic pain. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00420-020-01626-2.